THE EFFECT OF DRILL SHOOT TRAINING METHOD ON BOLABASKET TWO-POINT SHOOTING SKILLS - Ricardo Valentiono Latuheru; Sahabuddin Sahabuddin; H Herman (Universitas Majalengka, 2022)
This study aims to determine the influence of the drill shoot training method on basketball two-point shooting skills in extracurricular students of SMA Negeri 5 Makassar. This research is a type of experimental research, the population of this study is students of SMA Negeri 5 Makassar who participated in basketball extracurriculars, with a total sample of 20 students selected by random sampling. The data analysis techniques used are descriptive, normality, homogeneity, and t-test using SPSS Version 22.00 at a significant level of 95% or αo,o5. Based on the results of data analysis, this study concluded that there was an influence of the drill shoot training method on basketball two-point shooting skills in extracurricular students of SMA Negeri 5 Makassar experimental group as evidenced by an increase from a value of 24.20 increased to 26.85, with a calculated t value of 17, 667 and t table 2,093 (df 19).